Rain events based hillslope hydrological processes at the Langgewens Experimental Farm, Western Cape, South Africa - Wasserfall, Michiel Nicolaas (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.